The Elements of Badi’ in Arabic Poetry Writing Among Student of Maulana Malik Ibrahim State Islamic University Malang - Malikh, Majda Qudsiyatul; Hardiana, Wulan Nur; Kusuma, Nabela Pramesti; Ali, Arham; Wijayanti, Alvira Nirma (Borneo Journal of Language and Education, 2025)
Arabic is known for the beauty and richness of its rhetorical style, which is reflected in the harmony between meaning and expression. One of the branches of balaghah (Arabic rhetoric) is badi’, which focuses on the aesthetic value of both wording and meaning. This study aims to identify elements of badi’, particularly muhassinat lafdziyah (phonetic embellishments), in a poem written by a student of the State Islamic University of Maulana Malik Ibrahim Malang. The method used is a qualitative library research, with the data source in the form of the poems ‘Ākhir al-Bāb’ (The End of a Chapter), ‘Najmat Al-Ḥayāh’ (Star of Life), and the poem ‘Al-Ḥubbu Al-Muftakhir’ (The Exceptional Love). Data was collected through close reading techniques and analyzed using the Miles and Huberman model: data reduction, data display, and conclusion drawing. Data validation was carried out through peer discussion and increased persistence. The results of the study show that the poem contains several badi’ elements, including jinas (paronomasia), saja’ (rhymed prose), and muwazanah (parallelism). The implications of this research suggest that a badi’-based approach can serve as an effective strategy in teaching Arabic literary appreciation, particularly in enhancing students’ stylistic sensitivity and linguistic creativity. It is also hoped that this research will strengthen interest in reading and writing Arabic poetry among students and serve as a reference for developing Arabic language teaching methods based on literary aesthetics.